Implementasi Carbon Tax sebagai Strategi dalam Menekan Emisi Karbon: Dampaknya Bagi Corporate Sustainbility di Indonesia - Sari, Erma Wulan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Carbon emissions are one of the causes of climate change in the world. Carbon emissions have a negative impact on the environment, health and economy. Intervention from the government is needed in order to reduce carbon emissions in Indonesia. The purpose of this study is to determine the effectiveness of carbon tax implementation in reducing carbon emissions and its impact on the industrial world. The method used in this research is to use a qualitative descriptive method. The results of the research show that the implementation of carbon taxes in Indonesia will raise pros and cons for the community. Implementation of a carbon tax will have an impact on reducing carbon emissions which have a negative impact on the environment. With the imposition of a carbon tax, the industry will reduce fuel consumption so that carbon emissions can be reduced. In addition, with the implementation of a carbon tax, government revenue from the tax sector will also increase so that it can be used by the government to finance sustainable programs that can help mitigate climate change.